Inovasi Pengeringan Produk Pakan Ternak Menggunakan Mesin Rotary Dryer - Eny Boedi Orbawati; Fadlurrahman; Ari Mukti; Ikhwan Taufik (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2024)
The main issue faced by our partners is regarding the skin drying method for livestock feed raw materials. Until now, the applied drying method still relies on sunlight exposure. Many consider this method inefficient in terms of time and energy usage. The drying process takes several days. During the rainy season, drying becomes challenging, requiring repeated sun-drying for cassava skins to achieve thorough dryness. Production costs also increase. Moreover, there is room for improvement in the marketing process to boost the partner's business turnover. As a solution, the partners have adopted the use of a rotary dryer machine to replace the sunlight-based drying method. The partner's skills in using the rotary dryer machine and in marketing their products through digital marketing methods have also improved. According to our calculations, the partner's revenue target of 12,000,000 per year can be achieved. One of the supportive factors for implementing these activities is the partner's high level of cooperation during the execution of this service. This is evident through their timely attendance at events, contribution to the provision of cassava skin test materials, assistance with equipment shortages, and so forth.